Urban Expansion, Development Pressure And The Perception Of The Local Communities: The Application Of Geographic Information System (Gis) And Remote Sensing (Rs) - Khalid Sabbar, Mohammed (2013)
The rapid increase of urban development is a major issue for many regions around the world, which have resulted in astounding loss in agricultural and natural lands. Most developing countries face significant increase in demand for land to satisfy the need of urban activities for increase population densities and fast economic growth. In Malaysia, urbanization has increased from 27.6% in 1970 to 65.4% in 2000 and is projected to achieve 75.0% in 2020.This will cause significant changes in land use activities. Urban development process is one of many causes for land use changes, which has also caused rural environmental changes. Therefore, planners and policy makers should try to understand the urban expansion drivers in order to reduce or control the negative impacts of urban development. This study attempted to understand urban development pressure and investigate the impact on the affected communities. A multi-temporal analysis land use analysis was undertaken by using Remote Sensing (RS) and Geographical Information System (GIS). Textural analysis was performed using the satellite image to delineate the urban areas showing the movement of growth across the landscape through time. GIS and MCE approaches were that used to identify the suitable new development areas, which experiencing urban development pressure. Asocial economic survey was undertaken using two questionnaires where decision makers and Balik Pulau in Penang communities were interviewed. The survey was intended to investigate the perception of the community and to examine the future plans of affected Balik Pulau communities. This study found that the people in Balik Pulau have good perception; they identified urban development issues and have a good general level of awareness about various development issues, causes and consequences. The study found significant direct and indirect impact of urban development on rural environment of Balik Pulau. Generally, built-up areas experienced significant changes during several periods in size, speed and patterns of urban expansion. Penang Island in general and Balik Pulau in particular experienced an increase in size and concentration in built-up areas. Penang Island has many factors that created the development pressure on natural and agricultural land.